Vigilantisme Digital NCTzen: Praktik Cancel Culture Kasus Moon Taeil - Firando, Elvina Ekga; Pangastuti, Nurfitri Hafida; Paramitha, Aulia; Iwan, Iwan (Jurnal Media dan Komunikasi Indonesia, 2026)
This study aims to examine how digital vigilantism emerged as a form of cancel culture within the NCTzen fan community in response to the Moon Taeil case. This study focuses on understanding how the collective reaction of fans in the digital space transformed moral judgments into organized social action. The object of this study is the online behavior of NCTzen on social media platforms, specifically Instagram, TikTok, and X (formerly Twitter), after the emergence of the case. Using a qualitative approach with digital ethnography, this study relies on data from social media observation and in-depth interviews with two NCTzen members. Findings indicate that digital vigilantism operates through three main practices: pursuit, exploited visibility, and lateral surveillance, which collectively facilitate the emergence of boycott culture as a form of collective pressure. These practices enable fans to mobilize symbolic and social sanctions aimed at upholding shared moral values. The discussion shows that cancel culture functions both as a mechanism for expressing disappointment and as a means of strengthening solidarity and moral responsibility within the fandom. However, this study also highlights the ambiguous nature of these practices, as they simultaneously contribute to internal conflict and fragmentation among fans. In conclusion, this research shows that fandom communities have significant power in driving collective digital movements, positioning them as influential actors in contemporary digital culture.